Analysis of Entrepreneurial Knowledge, Financial Literacy and Motivation for Students' Entrepreneurial Intentions to Build A Startup Business - Husna, Nailal; Wardi, Yunia; Rino, Rino; Aulia Putri, Anjely (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2025)
This research aims to identify the influence of entrepreneurial knowledge, financial literacy, and motivation on students' entrepreneurial intentions at the Faculty of Economics and Business, Bung Hatta University. By using a data collection method by distributing questionnaires directly. The objects of this research were students at the Faculty of Economics and Business, Bung Hatta University, with a total sample of 105 people consisting of students majoring in accounting, management and development economics, which were processed with the help of the SE/17 statistical analysis tool. Based on the research results, it is known that the entrepreneurial knowledge variable has a positive effect on entrepreneurial intentions and the financial literacy variable has a positive effect on entrepreneurial intentions, while the motivation variable has no effect on the entrepreneurial intentions of students at the Faculty of Economics and Business, Bung Hatta University. Key : Entrepreneurial Intent, Entrepreneurial Knowledge, Financial Literacy, Motivation